Project policy and project outcomes: The moderating role of project leadership - Dominic Owusu; Dorcas Aba Ochil (Cogent Business & Management, 2023)
Ghana continues to record increasing numbers of uncompleted projects with its attendant cost overruns which are borne by the taxpayer. Several studies have sought to explain this phenomenon by exploring how project policy influences project outcomes. Though project leadership have been established to contribute to project outcomes, a study to look at how project leadership interplays between project policy and project outcome are lacking, hence the focus of this study. The current study thus uses PLS-SEM to model how project leadership interacts with project policy and project outcomes using government projects within the Cape Coast Metropolitan area. The study uses the resource-based view theory to explain the interactions among the variables. Data were collected from 97 project leaders who have worked on government projects within the Cape Coast Metropolis. The study found that project policies and transformational leadership styles enhance project outcomes. On the contrary transactional leadership style was found to adversely impact project outcomes. The study further concludes that leadership style does not moderate the relationship between project policies and project outcomes within the CCMA. It is, therefore, recommended that clear policies be formulated to guide the execution of government projects while project leaders are trained and admonished to employ the transformational leadership style to increase the success rate of government projects.
Keywords: 650; project leadership; project outcomes; project policy; transactional leadership; transformational leadership